Collective Liability in Corporate Crimes: A Conceptual Framework of Criminal Law - Madinah MokobombangInstitut (Journal of Innovative and Creativity, 2025)
This study examines the concept of collective responsibility in corporate crime through a comprehensive legal analysis that integrates a conceptual approach and a juridical-normative method within a library research framework. The research aims to construct a coherent theoretical model of corporate criminal liability that captures the complexity of modern organizational structures, decision-making processes, and the diffusion of mens rea within corporate environments. Conceptually, this study analyzes key theories such as identification theory, aggregation theory, corporate fault, vicarious liability, and organizational mens rea to explain how collective actions and systemic corporate cultures shape liability. Normatively, the study evaluates Indonesian positive law governing corporate criminal liability, identifies legal gaps related to collective responsibility, and examines court decisions as normative evidence. A comparative analysis with global practices further highlights best-practice models that may inform Indonesia’s legal reform. The findings indicate that Indonesia’s current framework remains fragmented and insufficient to address collective wrongdoing within corporations, requiring a more integrated conceptual model that combines structural, cultural, and normative elements of organizational behavior. This study concludes by proposing a conceptual framework to strengthen corporate criminal accountability and guide future legal policy development in Indonesia.